A Production and Operations management study on Flersan Shoes and Bags Manufacturing, Inc. - Atienza, Maria Jazmin (College of Engineering, 2000)
FLERSAN Shoes and Bags Manufacturing Incorporated were established in 1985 and is engaged in the production of shoes and ladies bags. Through time the company decided to concentrate on manufacturing of bags since the demand for shoes became low. The bags produced are sold locally in leading department stores and flea markets in the Philippines. The company could produce at an average of 1000 bags per week. Mr. Florencio B. Santos established and owns FLERSAN Shoes and Bags. The company?s mission and vision is to produce quality bags at a competitive price and at the same time provide employment. Using different techniques in Production and Operations Management, the group has documented the company?s system and procedures, production processes, capacity planning, facility layout, demand forecast and inventory management. Operations Management is the design, operation, and improvement of the production systems that create a firm?s primary products or services. Using streamline analysis and cause and effect diagrams, the group identified three major problems in FLERSAN. The first main problem is poor facility layout. The said problem causes faulty flow of operations and materials and unorganized workers and equipment. Absence of materials requirement planning is another major problem of the firm. This problem results to uncontrolled inventory level both for finished products and work-in-process, and sometimes stock out of raw materials occur. Lastly, the problem on improper aggregate planning was addressed. This problem causes high production cost and existence of idle time. Using the technique in facility layout designing, specifically REL charting, the group has come up with a suggested plant layout for FLERSAN. To avoid uncontrolled inventory, the group suggested a Materials Requirement Schedule for the firm. Set-up cost will be decreased in this case, since ordering would only be done once a month. Unlike in the present system, wherein orders are made at least twice a month. The group has also come up with different alternatives in aggregate plan for labor yields minimal cost, which is Php 1,521,805.00 compared to present system, which has a cost of Php 1,649,970.00. The said strategy employs 26 workers on lean season and applies chase strategy on peak seasons. The secret of the success of this study is the use of various techniques in Production and Operations Management as a tool in solving factory problems.